2021
DOI: 10.3390/su13179596
|View full text |Cite
|
Sign up to set email alerts
|

A Tool to Assess Architectural Education from the Sustainable Development Perspective and the Students’ Viewpoint

Abstract: Architectural education plays a fundamental role in achieving sustainable development by training future professionals who can contribute to sustainability through their practice. Nevertheless, to ensure the introduction of sustainable development in the education of future architects, it is fundamental to understand what is being done and what could be improved. Despite this, a big gap has been detected in the assessment of architectural education in Spain and worldwide. Thus, a close-ended questionnaire for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
(190 reference statements)
0
6
0
3
Order By: Relevance
“…Similarly, in ARCH 17,3 2002 and 2011, additional declarations were made in the UNESCO/UIA Validation System for Architectural Education, stressing the social responsibility of architecture and its significance in architectural education (UNESCO and UIA, 2011). Finally, after the declaration of UN 2030 Action in 2015, this action has been integrated into curricula through various pedagogical approaches at all levels (Celadyn, 2018;Boarin et al, 2020;Orlovic Lovren et al, 2020;Mart ınez-Ventura et al, 2021;Rajabifard et al, 2021;Calikusu et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, in ARCH 17,3 2002 and 2011, additional declarations were made in the UNESCO/UIA Validation System for Architectural Education, stressing the social responsibility of architecture and its significance in architectural education (UNESCO and UIA, 2011). Finally, after the declaration of UN 2030 Action in 2015, this action has been integrated into curricula through various pedagogical approaches at all levels (Celadyn, 2018;Boarin et al, 2020;Orlovic Lovren et al, 2020;Mart ınez-Ventura et al, 2021;Rajabifard et al, 2021;Calikusu et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is essential to comprehend what is going on and how it could be enhanced to ensure the incorporation of sustainable development into the education of future architects. Despite this, Mart ınez- Ventura et al (2021) have identified a significant gap in evaluating architectural education in Spain and worldwide. Their recommendations to education managers, teachers and policymakers focused on adjusting architectural education in Spain toward introducing or enhancing sustainable development.…”
Section: Arch 173mentioning
confidence: 99%
“…Un extracto del contenido de este apartado ha sido publicado en inglés enMartínez- Ventura et al (2021).…”
unclassified
“…Se tomó como referencia una versión del mapa de competencias no publicada, facilitada por el equipo investigador del proyecto-posterior a la versión presentada por Sánchez-Carracedo et al (2019) y anterior a la de Sánchez-Carracedo, Sureda et al (2021).147 Una traducción al inglés del mapa ha sido publicada enMartínez-Ventura et al (2021).…”
unclassified
See 1 more Smart Citation